2023
DOI: 10.1021/acsami.2c22231
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bubble Size Distribution on Nanostructured Ni Surfaces: Electrochemically Active Surface Area Versus Wettability

Abstract: Emerging manufacturing technologies make it possible to design the morphology of electrocatalysts on the nanoscale in order to improve their efficiency in electrolysis processes. The current work investigates the effects of electrodeattached hydrogen bubbles on the performance of electrodes depending on their surface morphology and wettability. Ni-based electrocatalysts with hydrophilic and hydrophobic nanostructures are manufactured by electrodeposition, and their surface properties are characterized. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…For example, the average bubble departure diameters on the flat electrode are 90, 104, 122, 143, and 146 μm at increasing current densities of −10, −30, −40, −70, and −100 mA/cm 2 , respectively. These average bubble departure diameters are consistent with findings reported by Krause et al, which range approximately from 80 to 140 μm. Previous studies attributed this to the enhanced local surface tension, greater drag force on bubbles, and a higher likelihood of adjacent bubble coalescence at high voltages or current densities.…”
Section: Resultssupporting
confidence: 92%
“…For example, the average bubble departure diameters on the flat electrode are 90, 104, 122, 143, and 146 μm at increasing current densities of −10, −30, −40, −70, and −100 mA/cm 2 , respectively. These average bubble departure diameters are consistent with findings reported by Krause et al, which range approximately from 80 to 140 μm. Previous studies attributed this to the enhanced local surface tension, greater drag force on bubbles, and a higher likelihood of adjacent bubble coalescence at high voltages or current densities.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the area of the CV curves obtained by the CuSn-30-3000 electrode is the largest (Figure c), suggesting that the as-fabricated CuSn-30-3000 electrode possesses the highest capacitance. This is possibly ascribed to its larger electrochemically active surface area (ECSA), as confirmed by the measurement of electrochemical double layer capacitance ( C dl ), which is positively correlated with ECSA . The C dl values of all electrodes were determined from the CV data by calculating the slopes of the current density versus scan rates in the non-Faradaic electrochemical double-layer region (SI, Figure S5), and these results are presented in Figure d.…”
Section: Resultsmentioning
confidence: 82%
“…The associated enhanced bubble detachment from the hydrophilic metal surface is also advantageous for other parts of the electrolyzer. For example, it was demonstrated that a quicker bubble detachment based on the hydrophilicity of laser-generated structures increases the performance of the electrocatalyst surface. , …”
Section: Discussionmentioning
confidence: 99%